High-molecular-weight kininogen and the intrinsic coagulation pathway in patients with de novo acute myocardial infarction - Cubedo, Judit; Ramaiola, Ilaria; Padró, Teresa; Martin-Yuste, Victoria; Sabate-Tenas, Manel; Badimon, Lina (Thrombosis and Haemostasis, 2013)
After an acute ischaemic event serum proteins may change reflecting the ischaemic damage. Proteomic studies could provide new insights into potential biomarkers in the evolution of ischaemic syndromes. In this study we have investigated the coordinated changes in coagulation-related proteins in the evolution after an acute myocardial infarction (AMI). Serum proteome (2D-electrophoresis and MALDI-TOF/ TOF) of AMI-patients within the first 6 hours after event onset (admission-time) and 3 days after were compared to controls. Systems biology and bioinformatic analysis were performed to identify the differentially expressed canonical pathways. In silico analysis of differential proteins revealed changes in the intrinsic coagulation pathway in the early phase post-AMI. The two identified high-molecular weight kininogen (HMWK) clusters were inversely correlated in AMI patients at admission, being the intensity of the low-molecular-weight form inversely related to myocardial necrosis (p<0.05). Factor XI (FXI) levels were decreased in AMI patients at admission and normalised 3 days after (p<0.05). There was an early increase in fibrinogen gamma and D-dimer at admission, followed by a decrease in fibrinogen turnover 3 days after (p<0.05). The influence of elapsed time of ischaemia on fibrinogen distribution changes was validated in coronary thrombi retrieved by thromboaspiration. In conclusion, our results demonstrate an active exchange between HMWK forms and a decrease in FXI indicative of intrinsic pathway activation, together with an increase in fibrinogen gamma turnover and D-dimer formation in the early phase post-AMI. Moreover, coronary thrombi showed a dynamic evolution in fibrinogen composition depending on the duration of ischaemia influencing serum fibrinogen-related products content.
Keywords: Acute myocardial infarction; high-molecular weight kininogen; fibrinogen; thrombus; proteomics